A national survey on community pharmacists’ perception, practice and perceived barriers towards pharmaceutical care services in the United Arab Emirates - Salma Mohamed; Subish Palaian; Muaed Alomar; Mohammad M. Al-Ahmad (Journal of Pharmaceutical Policy and Practice, 2025)
Background Pharmaceutical care (PC) is less practised in United Arab Emirates (UAE) community pharmacies. This study assessed community pharmacists’ (CPs) perceptions, practices and perceived barriers to providing PC.Methods A nationwide cross-sectional survey was conducted from May to October 2024 among CPs through direct visits, email invitations and WhatsApp groups. Customised version of a previously validated 5-point Likert-type questionnaire was used (Cronbach alpha = 0.93). Individual statements were scored 1–5, and Mann Whitney and Kruskal Wallis tests were performed to find the association between total perception, practice and barrier scores with demographic variables. Post hoc analyses and Kendall’s correlation were performed wherever applicable, at alpha = 0.05.Results A total of 227 CPs, with 70.9% (n = 161) of bachelor in pharmacy degree holders responded. The total median (IQR) scores for perception, practice and barriers were 24 (22–26)/30, 40 (34–45)/50 and 76 (63–86)/125, respectively. Most of the CPs felt that patients’ medications should be reviewed by them to prevent medicine-related errors and promote the appropriate medication use [median (IQR) 5 (4–5)]. They also felt that CPs are professionally skilled in providing PC [median (IQR) 5 (4–5)]. The major barrier reported was the lack of support from other health professionals toward PC [median (IQR) 4 (3–5)]. There was a statistically significant association between total perception scores with age (p = 0.023), work experience (0.036) and working hours (p = 0.012), total practice scores with work experience (p = 0.035) and training in PC (p = 0.009) and total barrier scores with the average number of CPs available in the shift (p = 0.002). A significant correlation was noticed within a few perception, practice and barrier constructs and between these constructs and participants’ demographic characteristics, p < 0.05.Conclusion Specific interventions at academic and regulatory levels targeting specific barriers are urgently needed with the incorporation of patient-centred care and interprofessional collaboration in academic and practice settings as the starting point.